2008
DOI: 10.1123/ijsnem.18.3.313
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Supplementation with Artichoke (Cynara scolymus L.) Extract on Selected Redox Parameters in Rowers

Abstract: High-intensity physical exercise decreases intracellular antioxidant potential. An enhanced antioxidant defense system is desirable in people subjected to exhaustive exercise. The aim of this study was to investigate the influence of supplementation with artichoke-leaf extract on parameters describing balance between oxidants and antioxidants in competitive rowers. This double-blinded study was carried out in 22 members of the Polish rowing team who were randomly assigned to a supplemented group (n = 12), rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 25 publications
(32 reference statements)
1
38
0
3
Order By: Relevance
“…If there was any doubt over whether the athletes were elite, the authors of the articles were emailed for further clarification; in total 14 authors were emailed. The methodology of the 59 elite athlete articles were then reviewed in detail (step 5), and 33 articles were excluded from the final review because of one or more of the following: the authors did not state the training status of the subjects, or respond to requests for subject details (n = 4) [38,46,73,74]; the subjects were masters/former athletes (n = 3) [75][76][77], amateur or college level athletes (n = 3) [ [78][79][80], athletes, but not elite status (n = 4) [42,48,81,82] or navy recruits (n = 1) [83]; participants were elite, but under 18 years of age (n = 2) [84,85]; only one sampling point was included, compared with healthy control data (n = 1) [86]; less than half of the study population were elite (n = 2) [87,88]; there were insufficient measures of redox balance [89,90] (n = 2); the training volume was not indicative of elite cyclists at 90 km per week (n = 1) [91]; the studies were RCTs involving antioxidant supplementation in elite athletes (n = 10) [92][93][94][95][96][97][98][99][100][101]. In addition, the methodological qualities of the articles were checked using methodological quality assessment criteria for the observational articles to be included in the final analysis (step 6).…”
Section: Study Selectionmentioning
confidence: 99%
“…If there was any doubt over whether the athletes were elite, the authors of the articles were emailed for further clarification; in total 14 authors were emailed. The methodology of the 59 elite athlete articles were then reviewed in detail (step 5), and 33 articles were excluded from the final review because of one or more of the following: the authors did not state the training status of the subjects, or respond to requests for subject details (n = 4) [38,46,73,74]; the subjects were masters/former athletes (n = 3) [75][76][77], amateur or college level athletes (n = 3) [ [78][79][80], athletes, but not elite status (n = 4) [42,48,81,82] or navy recruits (n = 1) [83]; participants were elite, but under 18 years of age (n = 2) [84,85]; only one sampling point was included, compared with healthy control data (n = 1) [86]; less than half of the study population were elite (n = 2) [87,88]; there were insufficient measures of redox balance [89,90] (n = 2); the training volume was not indicative of elite cyclists at 90 km per week (n = 1) [91]; the studies were RCTs involving antioxidant supplementation in elite athletes (n = 10) [92][93][94][95][96][97][98][99][100][101]. In addition, the methodological qualities of the articles were checked using methodological quality assessment criteria for the observational articles to be included in the final analysis (step 6).…”
Section: Study Selectionmentioning
confidence: 99%
“…The relatively recent advent of polyphenol supplementation for exercise studies has necessarily resulted in a fairly narrow range of doses. Nonetheless, a variety of polyphenol sources has been tested (see Table 4) [3751]. On the one hand this is interesting, but on the other does not allow for much comparison as only quercetin testing has resulted in several studies.…”
Section: Polyphenol Supplementation and Exercisementioning
confidence: 99%
“…Assessing these studies in chronological order, the first used chokeberry juice (11.5 mg of anthocyanins in 150 mL of juice, three times per day) [45] as supplement, TBARS were significantly reduced 24 h following a 2,000 m rowing ergometer test. The second study used an artichoke leaf extract administered in capsule form (400 mg of extract three times daily) for 5 weeks [51]. Artichoke leaves contain polyphenols in the phenolic acid and flavonoid groups.…”
Section: Polyphenols and Physiological Parametersmentioning
confidence: 99%
“…Numerous studies examined the effects of plant extract supplementation on oxidative stress in blood and other tissues, yet the findings are controversial. Interestingly, some studies have demonstrated the antioxidant effects of plant extracts (Voces et al 1999, 2004; Kim et al 2005), whereas some others have demonstrated the prooxidant effects of different plant extracts (Morihara et al 2006; Skarpanska-Stejnborn et al 2008, 2009; Halliwell 2008, 2011). …”
Section: Differential Effects Of Plant Antioxidants On Redox Status: mentioning
confidence: 99%